Efeitos das inomogeneidades da matéria em Cosmologias Aceleradas - Santos, Rose Clívia (2007)
The recent observational advances of Astronomy and a more consistent theoretical framework turned Cosmology in one of the most exciting frontiers of contemporary science. In this thesis, homogeneous and inhomogeneous Universe models containing dark matter and different kinds of dark energy are confronted with recent observational data. Initially, we analyze constraints from the existence of old high redshift objects, Supernovas type Ia and the gas mass fraction of galaxy clusters for 2 distinct classes of homogeneous and isotropic models: decaying vacuum and X(z)CDM cosmologies. By considering the quasar APM 08279+5255 at z = 3.91 with age between 2-3 Gyr, we obtain 0,2 < OM < 0,4 while for the j3 parameter which quantifies the contribution of A( t) is restricted to the intervalO, 07 < j3 < 0,32 thereby implying that the minimal age of the Universe amounts to 13.4 Gyr. A lower limit to the quasar formation redshift (zJ > 5,11) was also obtained. Our analyzes including flat, closed and hyperbolic models show that there is no an age crisis for this kind of decaying A( t) scenario. Tests from SN e Ia and gas mass fraction data were realized for flat X(z)CDM models. For an equation of state, úJ(z) = úJo + úJIZ, the best fit is úJo = -1,25, úJl = 1,3 and OM = 0,26, whereas for models with úJ(z) = úJo+úJlz/(l+z), we obtainúJo = -1,4, úJl = 2,57 and OM = 0,26. In another line of development, we have discussed the influence of the observed inhomogeneities by considering the Zeldovich-Kantowski-DyerRoeder (ZKDR) angular diameter distance. By applying the statistical X2 method to a sample of angular diameter for compact radio sources, the best fit to the cosmological parameters for XCDM models are OM = O, 26,úJ = -1,03 and a = 0,9, where úJ and a are the equation of state and the smoothness parameters, respectively. Such results are compatible with a phantom energy component (úJ < -1). The possible bidimensional spaces associated to the plane (a , OM) were restricted by using data from SNe Ia and gas mass fraction of galaxy clusters. For Supernovas the parameters are restricted to the interval 0,32 < OM < 0,5(20") and 0,32 < a < 1,0(20"), while to the gas mass fraction we find 0,18 < OM < 0,32(20") with alI alIowed values of a. For a joint analysis involving Supernovas and gas mass fraction data we obtained 0,18 < OM < 0,38(20"). In general grounds, the present study suggests that the influence of the cosmological inhomogeneities in the matter distribution need to be considered with more detail in the analyses of the observational tests. Further, the analytical treatment based on the ZKDR distance may give non-negligible corrections to the so-calIed background tests of FRW type cosmologies